Back to Baseline: Erectile Function Recovery after Radical Prostatectomy from the Patients' Perspective. (3rd April 2013) - Nelson, Christian J.; Scardino, Peter T.; Eastham, James A.; Mulhall, John P.
Abstract Introduction A variety of erectile function recovery (EFR) rates are reported post‐radical prostatectomy (RP), with some suggesting EFR rates over 90% [1]. Clinical experience suggests that patients view EFR as getting back to their baseline (BTB) erectile functioning (EF) without the use of medication. Aim This study explores EFR defined as BTB. Method Men pre‐RP and 24 months post‐RP completed the Erectile Function Domain (EFD) of the International Index of Erectile Function and one question on phosphodiesterase type 5 inhibitor (PDE5i) use. Men using a PDE5i at baseline were excluded. Main Outcome Measures At 24 m, "back to baseline" was defined as achieving the baseline EFD score (within 1 point or higher). Analyses included descriptive statistics, chi‐square, and logistic regression. Results One hundred eighty men had an average age at RP of 59 (SD = 7) years. When including men who were using a PDE5i at 24 months, 43% (N = 78, 95% CI: 36–51%) returned BTB. When considering BTB without the use of a PDE5i, 22% (N = 39, 95% CI: 16% to 28%) returned BTB. When focusing on a subset of men with baseline EFD ≥ 24 (N = 132), 36% (N = 47, 95% CI: 28% to 44%) returned BTB at 24 months using a PDE5i and 16% (N = 21, 95% CI: 11% to 23%) without the use of a PDE5i. For this group, there was a significant difference by age (<60 years, 23% vs. ≥60 years, 4%, P < 0.001), which remained a significant predictor (OR = 6.25, 95% CI: 1.88 to 50, P < 0.001) in multivariable analysis. Conclusions Twenty‐two percent of the entire sample and 16% of the men with functional (EFD ≥ 24) baseline erections returned to BTB EF without the use of medication. Only 4% of men who were ≥60 years old with functional erections pre‐surgery achieved BTB EF. Although gaining partial EF is also important, men pre‐RP should be educated on EFR and the chance of "back to baseline" EF.